Oral and Intravenous Fosfomycin for the Treatment of Complicated Urinary Tract Infections. (28th March 2020) - Zhanel, George G.; Zhanel, Michael A.; Karlowsky, James A.
Abstract : Oral fosfomycin is approved in Canada for the treatment of acute uncomplicated cystitis. Several studies have reported "off label" use of oral fosfomycin in the treatment of patients with complicated lower urinary tract infection (cLUTI). This review summarizes the available literature describing the use of oral fosfomycin in the treatment of patients with cLUTI. Collectively, these studies support the use of a regimen of 3 grams of oral fosfomycin administered once every 48 or 72 hours for a total of 3 doses for patients who have previously failed treatment with another agent, are infected with a multidrug-resistant (MDR) pathogen, or cannot tolerate first-line treatment due to intolerance or adverse effects. Additionally, a Phase 2/3 clinical trial, known as the ZEUS study, assessed the efficacy and safety of intravenous (IV) fosfomycin versus piperacillin-tazobactam in the treatment of patients with complicated upper urinary tract infection (cUUTI) or acute pyelonephritis (AP) including in patients with concomitant bacteremia. IV fosfomycin was reported to be noninferior to piperacillin-tazobactam in treating patients with cUUTI and AP; however, when outcomes were independently evaluated according to baseline diagnosis (i.e., cUUTI versus AP), IV fosfomycin was superior to piperacillin-tazobactam in the treatment of patients with cUUTI and demonstrated superior microbiological eradication rates, across all resistant phenotypes including extended-spectrum β -lactamase- (ESBL-) producing Escherichia coli and Klebsiella spp. and carbapenem-resistant (CRE), aminoglycoside-resistant, and MDR Gram-negative bacilli (primarily Enterobacterales ). Based on the ZEUS study, IV fosfomycin dosed at 6 grams every 8 hours for 7 days (14 days in patients with concurrent bacteremia) appears to be a safe and effective therapeutic option in treating patients with upper urinary tract infections, particularly those with cUUTI caused by antimicrobial-resistant Enterobacterales .